Enhanced Efficacy of Artemisinin Loaded in Transferrin‐Conjugated Liposomes versus Stealth Liposomes against HCT‐8 Colon Cancer Cells. (21st March 2016) - Leto, Isabella; Coronnello, Marcella; Righeschi, Chiara; Bergonzi, Maria Camilla; Mini, Enrico; Bilia, Anna Rita
Abstract: Artemisinin (ART) is a unique sesquiterpene lactone isolated from Artemisia annua that is well known for antimalarial properties and was recently reported as a promising anticancer drug. The aim of our work was to develop a novel nanocarrier for enhanced ART delivery and activation in cancer tissues, because transferrin receptors are largely expressed in cancer cells and the iron content is higher than in normal cells. ART was loaded in transferrin‐conjugated liposomes (ART‐L‐Tf), and the performance was compared with ART loaded in stealth liposomes (ART‐L). All of the liposomes were fully characterized in terms of size, drug‐entrapment efficiency, transferrin coupling moieties, and stability. Both cell uptake and cytotoxicity studies of the developed nanocarriers were tested in the HCT‐8 cell line, selected among several cell lines because of transferrin receptor overexpression. The results confirmed the enhanced delivery of ART‐L‐Tf in comparison with ART‐L in the targeting of the HCT‐8 cell line and an improved cytotoxicity as a result of the presence of iron ions, which resulted in concomitant synergism derived from the increased expression of transferrin receptors on the surface of the tumor cells. Abstract : Express delivery : A novel decorated liposome (L) was developed for selective artemisinin (ART) delivery and activation in cancer tissues, given their overexpression of transferrin (Tf) receptors (PEG: polyethylene glycol). Liposomes were characterized for size, drug‐entrapment efficiency, transferrin coupling moieties, and stability. Cell uptake and cytotoxicity were tested in the HCT‐8 cell line. We found enhanced selectivity and improved cytotoxicity, resulting in concomitant synergism.